Relationship among Short and Long Term of Hypoinsulinemia-Hyperglycemia, Dermatophytosis, and Immunobiology of Mononuclear Phagocytes - Thais F. C. Fraga-Silva; Camila M. Marchetti; Luiza A. N. Mimura; Gisele A. Locachevic; Márjorie A. Golim; James Venturini; Maria S. P. Arruda (Hindawi Limited, 2015)
Dermatophytes are fungi responsible for causing superficial infections. In patients with diabetes mellitus (DM), dermatophytosis is usually more severe and recurrent. In the present study, we aimed to investigate the influence of short and long term hypoinsulinemia-hyperglycemia (HH) during experimental infection by Trichophyton mentagrophytes as well as alterations in the mononuclear phagocytes. Our results showed two distinct profiles of fungal outcome and immune response. Short term HH induced a discrete impaired proinflammatory response by peritoneal adherent cells (PAC) and a delayed fungal clearance. Moreover, long term HH mice showed low and persistent fungal load and a marked reduction in the production of TNF-α by PAC. Furthermore, while the inoculation of TM in non-HH mice triggered high influx of Gr1+ monocytes into the peripheral blood, long term HH mice showed low percentage of these cells. Thus, our results demonstrate that the time of exposure of HH interferes with the TM infection outcome as well as the immunobiology of mononuclear phagocytes, including fresh monocyte recruitment from bone marrow and PAC activity.